2017
DOI: 10.1186/s13071-016-1954-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluralaner against Otodectes cynotis infestations in dogs and cats

Abstract: BackgroundThe efficacy of fluralaner for the treatment of Otodectes cynotis infestations in dogs and cats was evaluated after oral (dogs) or topical administration (dogs and cats).Twenty-four dogs and sixteen cats were experimentally infested with O. cynotis and randomly allocated to equal sized groups (n = 8/group). Dog groups were treated once, either orally with fluralaner at a minimum dose of 25 mg/kg body weight, topically with fluralaner at a dose of 25 mg/kg body weight or topically with saline solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
1
23
0
7
Order By: Relevance
“…The same methodology as already described by Taenzler et al [ 12 ] was applied to investigate the miticidal efficacy of the fixed combination of fluralaner plus moxidectin for the treatment of Otodectes cynotis infestations after topical application in cats and, therefore, only differences with regards to methods and study set-up described by Taenzler et al [ 12 ] are given below in detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same methodology as already described by Taenzler et al [ 12 ] was applied to investigate the miticidal efficacy of the fixed combination of fluralaner plus moxidectin for the treatment of Otodectes cynotis infestations after topical application in cats and, therefore, only differences with regards to methods and study set-up described by Taenzler et al [ 12 ] are given below in detail.…”
Section: Methodsmentioning
confidence: 99%
“…Of the isoxazoline class, sarolaner is the only member in combination with selamectin, which is registered for the treatment of Otodectes mites in cats, with a re-treatment interval of 4 weeks. The efficacy of fluralaner as a single agent, with a 3 months re-treatment interval, against Demodex , Sarcoptes and Otodectes mites in dogs [ 10 12 ] and Otodectes mites in cats [ 12 ] has been reported previously.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, Walther et al (2016) described fluralaner for spot-on administration in cats as a safe formulation, allowing pharmacological associations to be made without the risk of clinical changes. Taenzler et al (2017) also reported that spot-on administration of a fluralaner-based formulation in cats provoked no adverse effects. In the present study, with afoxolaner no adverse effects being observed in any of the animals treated.…”
Section: Discussionmentioning
confidence: 94%
“…Both have long residual activity and act systemically covering ectopic infestation . Good treatment results also have been reported for orally administered and systemically active drugs of the isoxazoline class in small‐scale studies with induced infestation with ear mites in dogs . Sarolaner is approved in Europe, in combination with selamectin, for the treatment of O. cynotis infestations in cats …”
Section: Introductionmentioning
confidence: 90%